2023
DOI: 10.3390/s23094354
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Metrics of Surgical Difficulty and Multi-Task Requirement during Robotic Surgery Skills

Abstract: Previous studies in robotic-assisted surgery (RAS) have studied cognitive workload by modulating surgical task difficulty, and many of these studies have relied on self-reported workload measurements. However, contributors to and their effects on cognitive workload are complex and may not be sufficiently summarized by changes in task difficulty alone. This study aims to understand how multi-task requirement contributes to the prediction of cognitive load in RAS under different task difficulties. Multimodal phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Asia is the continent with the largest proportion of publications, with five studies published in China [4,46,49,51,53] and one in Turkey [50], representing 60% of the articles selected in the sample. The secondhighest number of publications was in the USA (20%) [47,52]. Finally, two articles in the last 10 years were published in Europe (20%): one in Spain in 2023 [3] and another in Denmark in 2019 [49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asia is the continent with the largest proportion of publications, with five studies published in China [4,46,49,51,53] and one in Turkey [50], representing 60% of the articles selected in the sample. The secondhighest number of publications was in the USA (20%) [47,52]. Finally, two articles in the last 10 years were published in Europe (20%): one in Spain in 2023 [3] and another in Denmark in 2019 [49].…”
Section: Resultsmentioning
confidence: 99%
“…The largest sample in the studies was 78 subjects [49], while the smallest sample had 10 participants [47]. The total number of participants in the selected studies was 416 subjects (M = 41.6, SD = 24.4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al investigated how live data acquired during any robotic endoscopic surgical procedure may be used to correct inaccurate FEM simulation results using an open-source da Vinci Surgical System to probe a soft tissue phantom and replay the interaction in simulation. They trained a neural network to correct for the difference between the predicted mesh position and the measured point cloud and showed improved FEM results by 15–30% over various simulation parameters [ 35 ].…”
Section: Ai In Robotic Surgical Assessment and Feedbackmentioning
confidence: 99%
“…Multimodal sensing outperformed individual sensors for predicting cognitive load. Lim et al demonstrated that EEG spectral analysis could distinguish the cognitive workload of a surgeon not only relating to surgical task difficulty but also to multi-tasking requirement [ 42 ].…”
Section: Measurement Toolsmentioning
confidence: 99%